2017
DOI: 10.6061/clinics/2017(03)09
|View full text |Cite
|
Sign up to set email alerts
|

The acceptability of vaginal smear self-collection for screening for cervical cancer: a systematic review

Abstract: Cervical cancer is a major cause of death in adult women. However, many women do not undergo cervical cancer screening for the following reasons: fear, shame, physical limitations, cultural or religious considerations and lack of access to health care services. Self-collected vaginal smears maybe an alternative means of including more women in cervical cancer screening programs. The objective of this systematic review was to evaluate the acceptability of vaginal smear self-collection for cervical cancer screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
1
26
0
2
Order By: Relevance
“…These different options are also associated with different recommended intervals between screens (e.g., 3 years for a Pap test, 5–6 years for an HPV test), and different ages to start and stop screening. Recent systematic reviews suggest that most women find self-sampling preferable to clinician-collected sampling (Braz et al, 2017; Nelson et al, 2017; Racey, Withrow, & Gesink, 2013; Verdoodt et al, 2015) because of factors related to ease, ability to conduct the testing without a health care professional or by themselves, privacy, and lack of embarrassment.…”
mentioning
confidence: 99%
“…These different options are also associated with different recommended intervals between screens (e.g., 3 years for a Pap test, 5–6 years for an HPV test), and different ages to start and stop screening. Recent systematic reviews suggest that most women find self-sampling preferable to clinician-collected sampling (Braz et al, 2017; Nelson et al, 2017; Racey, Withrow, & Gesink, 2013; Verdoodt et al, 2015) because of factors related to ease, ability to conduct the testing without a health care professional or by themselves, privacy, and lack of embarrassment.…”
mentioning
confidence: 99%
“…Beyond the studies included in this review which focused on immigrant women, ample research has demonstrated that self-collection for HPV testing, regardless of device, is generally both feasible and acceptable for women across the globe (Arbyn et al, 2018;Braz et al, 2017;Nelson et al, 2017). The researchers whose papers were included in this review have begun to explore whether self-collection for HPV testing could help to overcome barriers to CCS for immigrant women who are persistently at risk for being under-screened in their countries of resettlement.…”
Section: Discussionmentioning
confidence: 99%
“…The literature is similarly divided, such that some authors believe that self-sampling should be an option available to all eligible women (not just non-responders) 39,40 , while others suggest that self-sampling is appropriate only as a strategy to reach "non-compliant" women 24,41 , and yet others argue that self-sampling is not the best way to reach under-or never-screened groups 22,42 . Recent evidence syntheses suggest that most women find self-sampling preferable to clinician-collected sampling 23,43 . Other systematic reviews found that self-sampling could increase cervical screening coverage in under-or never-screened women 24 , though some authors observed similar uptake rates in opt-in scenarios 44 .…”
Section: Discussionmentioning
confidence: 99%